Strengthening students’ academic digital competencies through development of learning patterns: A Danish national project (STAK) - Brink, Helle; Wind, Charlotte; Nilson, Ulla Buch; Sejersen, Dorthe Brauner; Carlsen, Lisbeth Ramsgaard (Septentrio Conference Series, 2020)
Today students are met with expectations of being able to navigate in a broad spectre of digital challenges. The STAK project aims at developing specific digital didactic designs in the form of learning patterns that support and develop students' digital competencies, within areas such as digital sharing, open access, online collaboration and other emerging technological opportunities and challenges. The concept of “Learning Patterns” covers a method used to capture experience about best practice from educators and other experts, and disseminate these into concrete learning patterns and activities. These concrete learning patterns are then systematised and described in such a way that it is possible for others to understand them and reuse them. As a product, learning patterns can be described as a “how-to”-formula that you can transfer to your own teaching. The STAK project aims at developing approximately 300 learning patterns within four categories: Digital information competencies, digital participatory competencies, digital production competencies, and digital responsibility- and security competencies. As the STAK project progresses, the concrete learning patterns will be available on an OER (open educational resource) along with models and templates for how to develop learning patterns. In the presentation, we focus on our work processes with developing learning patterns in the project and present a concrete learning pattern. We are also going to provide you with insight into how you can use this method to develop your own learning patterns.